Enti ecclesiastici e affidamento di contratti pubblici - Licastro, Angelo (2022)
Ecclesiastical bodies and awarding of public procurement · This paper explores the possibility of extending civil law rules on public procurement to church-bodies. Towards that aim, the question whether ecclesiastical entities can claim themselves as ‘public law bodies’ (« organismi di diritto pubblico ») under the law is explored. As will be seen, elements to answer this question can be found in an advice by the National Anti- Corruption Authority to the effect that church-bodies can be de facto private entities serving the public interest under public procurement rules.
Keywords: Public Procurement; Ecclesiastical Bodies; Body Governed by Public Law